Pembelajaran Berbasis Kompetensi Bagi Pengusaha Kuliner - Dyah Kusumastuti; Friday Fitricia Nur (Jurnal Manajemen dan Bisnis Indonesia, 2014)
Entrepreneurship its meaning two things: entrepreneurship as a career opportunity, or as competency. This study aims to analyze the needs of culinary competencies for successful entrepreneurs have the superior performance and how entrepreneurial learning competency for culinary entrepreneurs . Research Methods by doing Competency Based Interview with models of entrepreneurship competencies include : Achievement , Thinking and Problem Solving , Personal Maturity , Influence , Directing & Controlling, Orientation to others of the 18 samples of culinary successful entrepreneur in the city and around Bandung - West Java . The finding that there is a need for competency 6 competencies and 14 culinary skills . Furthermore, Competency Based Learning ( CBL ) starting by identifying Skills Competency, Competency Based Learning Requirements ( ( CBLRs) and lessons are required. Competency evaluation conducted by Competency Based Assessment ( CBA ) of " behavior that arises from the CBL . CBL needs to be done to stimulate entrepreneurial culinary talent and motivate to become entrepreneurs and to develop new innovation that will create jobs , create economic and social wealth . As the government's accelerated learning should be the initiator for building entrepreneurial learning culinary that can be accessed by culinary entrepreneurs which is required to develop competency and stimulate innovation . Key Word: Learning, Competency, Entrepreneurship, Culinary